Characteristics and associated factors with sports injuries among children and adolescents - Vanderlei, Franciele M.; Vanderlei, Luiz C. M.; Bastos, Fabio N.; Netto Júnior, Jayme; Pastre, Carlos M. (Associação Brasileira de Pesquisa e Pós-Graduação em Fisioterapia, 2014)
BACKGROUND: The participation of children and adolescents in sports is becoming increasingly common, and this increased involvement raises concerns about the occurrence of sports injuries. OBJECTIVES: To characterize the sports injuries and verify the associated factors with injuries in children and adolescents. METHOD: Retrospective, epidemiological study. One thousand three hundred and eleven children and adolescents up to 18 years of age enrolled in a sports initiation school in the city of Presidente Prudente, State of São Paulo, Brazil. A reported condition inquiry in interview form was used to obtain personal data and information on training and sports injuries in the last 12 months. Injury was considered any physical complaint resulting from training and/or competition that limited the participation of the individual for at least one day, regardless of the need for medical care. RESULTS: The injury rate per 1000 hours of exposure was 1.20 among the children and 1.30 among the adolescents. Age, anthropometric data, and training characteristics only differed with regard to the presence or absence of injuries among the adolescents. The most commonly reported characteristics involving injuries in both the children and adolescents were the lower limbs, training, non-contact mechanism, mild injury, asymptomatic return to activities, and absence of recurrence. CONCLUSIONS: The injury rate per 1000 hours of exposure was similar among children and adolescents. Nevertheless, some peculiarities among adolescents were observed with greater values for weight, height, duration of training, and weekly hours of practice.
Keywords: child; adolescent; traumatism in athletes; risk factors; rehabilitation